2021
DOI: 10.21608/asejaiqjsae.2021.183461
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Relief and Growth-Promoting Effect of Sweet Pepper Plants (Capsicum annuum L.) by Glutathione, Selenium, and Humic Acid Application

Abstract: Three pot experiments were carried out at a private farm in Abu Homos, El-Beheira Governorate during 2018 and 2019 and 2020 growing seasons to examine the role of Glutathione, Selenium, and Humic Acid solely in the first two seasons and in combinations in the third season in elevation the impact of salinity on vegetative growth (leaves fresh weight, leaves dry weight and leaf area), chemical composition (chlorophyll, N, P, Ca, K, Na, Proline contents, K/Na ratio) and yield of sweet pepper cultivar "Madrid". Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…They can be categorized into 7 main groups: protein hydrolysates and N-containing compounds, botanical extracts, inorganic compounds, humic and fulvic acids, biopolymers, beneficial fungi and bacteria ( du Jardin, 2015 ). Among the seven types of biostimulants, four of them from the groups, protein hydrolysates and N-containing compounds, botanical extracts, inorganic compounds, humic and fulvic acids, were combined with GSH to investigate their combined effects on plants in response to abiotic stresses such as salinity and metal toxicity ( Dawood et al, 2020 ; Elkhatib et al, 2021 ; Jahan et al, 2021 ; Rehman et al, 2021 ). A brief introduction and key results of the combined application of GSH and biostimulants were elaborated in the subsections below.…”
Section: Sequenced or Combined Application Of Gsh And Bioactive(s)mentioning
confidence: 99%
See 4 more Smart Citations
“…They can be categorized into 7 main groups: protein hydrolysates and N-containing compounds, botanical extracts, inorganic compounds, humic and fulvic acids, biopolymers, beneficial fungi and bacteria ( du Jardin, 2015 ). Among the seven types of biostimulants, four of them from the groups, protein hydrolysates and N-containing compounds, botanical extracts, inorganic compounds, humic and fulvic acids, were combined with GSH to investigate their combined effects on plants in response to abiotic stresses such as salinity and metal toxicity ( Dawood et al, 2020 ; Elkhatib et al, 2021 ; Jahan et al, 2021 ; Rehman et al, 2021 ). A brief introduction and key results of the combined application of GSH and biostimulants were elaborated in the subsections below.…”
Section: Sequenced or Combined Application Of Gsh And Bioactive(s)mentioning
confidence: 99%
“…Among the elements, the role of Se in alleviating stress-induced damage through activation of the antioxidant defense system in plants has been explored and studied ( Chu et al, 2010 ; Jiang et al, 2017 ). These studies demonstrated the significance of Se as an antioxidant and a cofactor of the enzyme GPX, catalyzing the reduction of H 2 O 2 , which is overproduced when the plants are under stress ( Elkhatib et al, 2021 ). Besides that, Se can control the permeability and changes in activities in a plant cellular membrane ( Dawood et al, 2020 ).…”
Section: Sequenced or Combined Application Of Gsh And Bioactive(s)mentioning
confidence: 99%
See 3 more Smart Citations